Gut microbiota: A bridge between depression and cardiovascular disease-A narrative review - Xingdou Mu; Lele Feng; Hong Li; Yang Sun (The Microbe)
Background: Depression and cardiovascular disease (CVD) exhibit a bidirectional relationship, with individuals suffering from either condition facing elevated risks of comorbidity and mortality. Emerging evidence highlights the gut microbiota (GM) as a critical mediator in this interaction. Methods: This narrative review synthesizes current research on the role of GM and its metabolites in linking depression and CVD. Results: Dysbiosis of GM is consistently observed in both conditions, characterized by reduced microbial diversity, decreased abundance of beneficial bacteria (e.g., Faecalibacterium, Roseburia), and increased pro-inflammatory species (e.g., Enterobacteriaceae). Key microbial metabolites, including short-chain fatty acids (SCFAs), trimethylamine N-oxide (TMAO), and indole-3-propionic acid (IPA), influence neuroendocrine, immune, and metabolic pathways. For instance, SCFAs modulate neuroinflammation and endothelial function, while TMAO exacerbates atherosclerosis. Depression-associated GM alterations disrupt the gut-brain axis via the hypothalamic-pituitary-adrenal (HPA) axis and vagus nerve, whereas CVD-related dysbiosis promotes systemic inflammation and endothelial dysfunction. Shared mechanisms, such as NLRP3 inflammasome activation and bile acid metabolism dysregulation, further connect these diseases. Therapeutic strategies targeting GM probiotics, dietary interventions, fecal microbiota transplantation (FMT), and metabolite modulation may alleviate both conditions. However, challenges remain in addressing heterogeneity across studies, establishing causal relationships, and optimizing personalized interventions. Future research should integrate multi-omics approaches and longitudinal studies to unravel the gut-brain-heart axis, paving the way for precision therapies. Conclusions: This review underscores GM’s pivotal role in depression and CVD comorbidity, offering novel insights for clinical management and interdisciplinary treatment strategies.